The effect of time–space compression in the Yangtze River Delta region under transportation integration: An accessibility-based analysis - Shuo Shang; Haibing Jiang (PLoS ONE, 2026)
The Yangtze River Delta (YRD) region is one of the areas in China with the highest level of transportation integration, featuring a well-developed high-speed rail network, multimodal transport system, interconnected intercity bus services, and intelligent transportation platforms. These developments have brought about significant effects of time-space compression in the region. Under the effects of time-space compression, the changes in the regional socio-economic spatial structure are worth further exploration. To this end, from the perspective of accessibility, this study explores the time–space compression effect in the YRD region using models such as economic linkage strength (ELS), central city isochronous-ring, daily accessibility (DA), and employment accessibility (EA) indicators. The results show: (1) The time distance between central cities and prefectural-level and lower-tier cities has greatly decreased, resulting in a network-based structure and a trend towards urban system flattening; within 1–2 hours of central cities, the scale of the population, number of cities, and regional coverage area have rapidly expanded, promoting regional integration and urban agglomeration. (2) Intercity time-space compression has significantly increased the total ELS between cities, intensifying the “strong center” economic linkage pattern. The radiation and driving capacity of central cities for the region has notably increased, and the equilibrium of urban economic linkage capabilities has improved. (3) Time-space compression strengthens the “competitive-cooperative effect” of central cities, facilitating the convenient sharing and equalization of high-quality urban public services, but also leading to tensions in the supply and demand of these resources. (4) A high-accessibility region has formed in the “Shanghai-Nanjing-Hangzhou” triangle, where high-accessibility cities possess larger market hinterlands and more employment opportunities, providing significant opportunities for the rise of small and medium-sized cities in peripheral areas. Based on these findings, in the context of time-space compression, these regions should actively build convenient, efficient, and resilient commuting and transfer networks. A networked spatial development strategy should be implemented, establishing efficient regional collaboration mechanisms and public service cooperation systems to promote coordinated regional development.